Three Cases of Spine Fractures after an Airplane Crash - Lee, Han Joo (Korean J Neurotrauma, 2015)
While injuries to the spine after an airplane crash are not rare, most crashes result in fatal injuries. As such, few studies exist that reported on spine fractures sustained during airplane accidents. In this report, we demonstrate three cases of spine fractures due to crash landing of a commercial airplane. Three passengers perished from injuries after the crash landing, yet most of the passengers and crew on board survived, with injuries ranging from minor to severe. Through evaluating our three spine fracture patients, it was determined that compression fracture of the spine was the primary injury related to the airplane accident. The first patient was a 20-year-old female who sustained a T6-8 compression fracture without neurologic deterioration. The second patient was a 33-year-old female with an L2 compression fracture, and the last patient was a 49-year-old male patient with a T8 compression fracture. All three patients were managed conservatively and required spinal orthotics. During the crash, each of these patients were subjected to direct, downward high gravity z-axis (Gz) force, which gave rise to load on the spine vertically, thereby causing compression fracture. Therefore, new safety methods should be developed to prevent excessive Gz force during airplane crash landings.